Potential role of two novel agonists of thyroid hormone receptor‐β on liver regeneration. (29th April 2020) - Perra, Andrea; Kowalik, Marta Anna; Cabras, Lavinia; Runfola, Massimiliano; Sestito, Simona; Migliore, Cristina; Giordano, Silvia; Chiellini, Grazia; Rapposelli, Simona; Columbano, Amedeo
Abstract: Objectives: Although the hepatomitogenic activity of triiodothyronine (T3) is well established, the wide range of harmful effects exerted by this hormone precludes its use in liver regenerative therapy. Selective agonists of the beta isoform of thyroid hormone receptor (TRβ) do not exhibit T3‐induced cardiotoxicity and show a good safety profile in patients with NASH. The aim of this study was to investigate whether two novel TRβ agonists, the prodrug TG68 and the active compound IS25 could stimulate hepatocyte proliferation without T3/TRα‐dependent side effects. Methods: Rats were treated with three different doses (12.5, 25 and 50 μg/100 g body weight) for one week. Hepatocyte proliferation, liver injury and serum biochemical parameters were measured by immunohistochemistry, qRT‐PCR and Western blot. Results: Both drugs increased hepatocyte proliferation as assessed by bromodeoxyuridine incorporation (from 14% to 28% vs 5% of controls) and mitotic activity. Enhanced proliferation occurred in the absence of significant signs of liver injury as shown by lack of increased serum transaminase levels or of apoptosis. No cardiac or renal hypertrophy typically associated with treatment with T3 was observed. Importantly, no proliferation of pancreatic acinar cells, such as that seen after administration of T3 or the TRβ agonist GC1 was detected following either TG68 or IS25, demonstrating the hepato‐specificity of these novel TRβ agonists. Conclusions: The present study shows that TG68 and IS25 induce massive hepatocyte proliferation without overt toxicity. Hence, these agents may have a significant clinical application for regenerative therapies in liver transplantation or other surgical settings.